Molecular detection of pathogenic leptospiral protein encoding gene (lipL32) in environmental aquatic biofilms. (18th February 2016) - Vinod Kumar, K.; Lall, C.; Vimal Raj, R.; Vedhagiri, K.; Vijayachari, P.
Abstract: Leptospirosis is a zoonotic disease often encountered during post–monsoon season due to exposure with contaminated water. Leptospires have long been regarded as solitary organisms that persist in soil and aquatic environments. Here, the presence of leptospires in the aquatic biofilm exposed in the paddy field, sewers and stagnant rain water was demonstrated. Biofilm samples from paddy field water, submerged paddy leaves, sewers and stagnant rain waters from urban and rural areas were collected. Total genomic DNA was extracted and pathogenic leptospiral specific gene amplification was carried out to determine the spatial distribution of the bacteria. The degree of pathogenic Leptospira in biofilms from paddy field surface water, submerged leaf, were 33·3% and 27·2% respectively, whereas in rural and urban area, the sampling sites such as stagnant rain water, domestic sewer and collective sewers showed 11·1%, 13% and 16·6% with leptospires respectively. Higher proportion of pathogenic Leptospira in aquatic ecosystems, such as paddy field, could be one of the main factors for the occurrence of disease, more among the agricultural workers. This study would help to identify various survival strategies of leptospires in the environment and thus disease transmission. Significance and Impact of the Study: Little is known regarding the mechanisms by which pathogenic leptospires persist in aqueous environment, outside the mammalian host. In this view this is the first report of the distribution of Leptospira in environmental biofilm such as sewers and paddy leaf surfaces. This ability of pathogenic Leptospira to survive in aquatic ecosystems especially in biofilms could be one of the main factors which facilitate its survival in the environment, and thus disease transmission among the risk groups, such as sewage and agriculture worker. This study will encourage researchers in the field to consider biofilm as an important factor, when detecting leptospires in environment. Abstract : Significance and Impact of the Study: Little is known regarding the mechanisms by which pathogenic leptospires persist in aqueous environment, outside the mammalian host. In this view this is the first report of the distribution of Leptospira in environmental biofilm such as sewers and paddy leaf surfaces. This ability of pathogenic Leptospira to survive in aquatic ecosystems especially in biofilms could be one of the main factors which facilitate its survival in the environment, and thus disease transmission among the risk groups, such as sewage and agriculture worker. This study will encourage researchers in the field to consider biofilm as an important factor, when detecting leptospires in environment.